Thyroid autoimmunity and autoimmunity in chronic spontaneous urticaria linked to disease severity, therapeutic response, and time to remission in patients with chronic spontaneous urticaria - Kumutnart Chanprapaph (2019)
Copyright © 2018 Kumutnart Chanprapaph et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. Background. Chronic spontaneous urticaria (CSU) is autoimmune in nature and associated with thyroid autoimmunity (TA), but evidence on autoimmunity in relation to CSU progression and prognosis is limited. We evaluated whether TA and autoimmunity in CSU are correlated with disease severity, therapeutic response, and time to remission and establish an association between CSU characteristics linked to thyroid autoantibody. Methods. Medical records of patients diagnosed with urticaria attending outpatient dermatology clinic at a university-based hospital from 2013 to 2017 were retrospectively reviewed. Data on the clinical characteristics, laboratory investigations particularly thyroid antibody titers, autologous serum skin test (ASST) and autologous plasma skin test (APST) results and their link to disease severity, treatments, and time to remission of CSU patients were analyzed. Results. Of 1,096 patients with urticaria, 60.2% had CSU. Three-hundred patients fulfilled the inclusion criteria for CSU with complete thyroid antibody testing. Positive TA was significantly associated with female gender and age > 35 years (p = 0.008). Antithyroid peroxidase (anti-TPO)-positive patients suffered from CSU longer than 12 and 18 months compared to anti-TPO-negative patients (100.0% vs. 82.6%, p = 0.042, and 100.0% vs. 75.9% p = 0.020, respectively). The presence of urticarial attacks > 4 days/week was significantly seen in ASST and APST-positive patients compared to those without (84.6% vs. 61.3%, p = 0.011, and 85.3% vs. 61.8%, p = 0.006, respectively). Positive APST patients were more difficult to treat than those with negative results (61.2% vs. 37.8%, p = 0.017). Conclusions. Antithyroid peroxidase is a predictor of time to remission, while autologous skin testing is linked to disease severity (ASST and APST) and therapeutic response (APST) in CSU patients.